2019
DOI: 10.18502/jad.v12i4.354
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal Activity of Essential Oil of Syzygium aromaticum (Clove) in Com-parison with Its Major Constituent, Eugenol, against Anopheles stephensi

Abstract: Background: In this study, larvicidal activity of clove essential oil (EO), as a green and relatively potent larvicide, was compared with its main constituent, Eugenol, against Anopheles stephensi. Methods: High-performance liquid chromatography (HPLC) was used to determine the amount of eugenol, major constituent of clove EO. In addition, larvicidal activity of clove EO and eugenol was evaluated against An. stephensi. Results: The amount of eugenol in clove EO was determined as 67% using HPLC anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 36 publications
0
17
0
2
Order By: Relevance
“…Regarding the mode of action, several mechanisms through which essential oils produce neurotoxic effects have been proposed, such as EOs acting on GABA receptors, octopamine receptors, or acetylcholinesterase [30]. Further, the synergistic effect of the essential oil constituents likely increases their larvicidal activity [31][32][33]. Scalerandi et al proposed an interesting mode for synergistic effects using the metabolic model [34].…”
Section: Chemical Composition Of Essential Oilsmentioning
confidence: 99%
“…Regarding the mode of action, several mechanisms through which essential oils produce neurotoxic effects have been proposed, such as EOs acting on GABA receptors, octopamine receptors, or acetylcholinesterase [30]. Further, the synergistic effect of the essential oil constituents likely increases their larvicidal activity [31][32][33]. Scalerandi et al proposed an interesting mode for synergistic effects using the metabolic model [34].…”
Section: Chemical Composition Of Essential Oilsmentioning
confidence: 99%
“…aegypti larvae was also found with LC 50 values of 37.8 and 54.0 ppm after 24 h . Osanloo et al . demonstrated that the LC 50 value of eugenol against Anopheles stephensi was 86.96 ppm, while the LC 90 value was 128.18 ppm.…”
Section: Discussionmentioning
confidence: 89%
“…Many plant species have pharmacological activities attributable to their phytoconstituents, for instance, glycosides, saponins, flavonoids, steroids, tannins, alkaloids and terpenes (Batiha et al, 2020). CEO includes many components such as flavonoids, alkaloids and monoterpenes, and has broad pharmacological efficacy (Osanloo, Sedaghat, Esmaeili, & Amani, 2018; Salim, 2017). Furthermore, the pharmacological effects of mentioned constituents are different, for example, the main site action of flavonoids is acetylcholinesterase (Perumalsamy, Jang, Kim, Kadarkarai, & Ahn, 2015), as well as alkaloids and monoterpenes target Na‐K‐ATPase or Na + and K + channels (Lucia, Zerba, & Masuh, 2013; Rajashekar & Shivanandappa, 2017).…”
Section: Discussionmentioning
confidence: 99%